High-Risk Human Papillomaviruses in Oral Squamous Cell Carcinoma (OSCC): A Meta-Analysis - Ambreen wasim; Shumaila usman; Talat Mirza (ziauddin University, 2020)
Background: The prevalence of high-risk Human Papillomaviruses (HPV) in cases of oral cavity squamous cell carcinoma (OSCC) varies widely. Therefore, the aim of this study was to determine the pooled prevalence of all high-risk HPV by meta-analysis with specific emphasis on HPV type 16/18. Methods: The studies were retrieved from PubMed and MEDLINE to conduct a comprehensive literature review on HPV detection in OSCC. Search terms included, High-risk HPV, oral cancer, polymerase chain reaction (PCR), in situ hybridization (ISH). We reviewed 47 research studies systematically to report the prevalence of high-risk HPV infection in oral cancer. Included studies published from 1988 to 2018. The meta-analysis was carried out by using MedCalc software version 19.0.3. Results: A meta-analysis was executed to calculate the pooled prevalence of High-risk HPV types, which revealed overall decreasing order frequency of high-risk HPV and high-risk type displaying the highest number of type16/18 HPV in the reported cases. As 30.71% [24.59 to 37.19 % confidence interval (CI) at 95%] and 28.88 % [22.62 to 35.57% confidence interval (CI) at 95%] followed by other high-risk HPV 3.59% [2.22 to 5.46%] respectively. Conclusions: According to present meta-analysis, we conclude that 16/18 HPV displaying maximum infection rate as compared to other high-risk HPV type in OSCC cases.